AutoCAD 2021 beginning and intermediate - Hamad, Munir M. (Mercury Learning and Information, 2020)
This book is the most comprehensive book you will find on AutoCAD 2021 - 2D Drafting on the market. It is divided into three major parts: Essentials: From Chapter 1 to Chapter 10. It assumes that the reader has no previous experience in AutoCAD; hence it starts from scratch. Chapter ten contains three projects--one architectural and two mechanical using both Imperial and metric units. -- Intermediate: From Chapter 11 to Chapter 18. It contains a deeper discussion on a subject we touched on in the Essentials part, or a new advance feature. -- Advanced: from Chapter 19 to Chapter 26. It discusses the most advanced features of AutoCAD 2021. If you don't have any prior experience in AutoCAD this book is a perfect start, and you can stop at the end of any part. This book is also a good source to prepare for the AutoCAD Certified Professional exam.